ACUTE MOTOR AXONAL NEUROPATHY IN A CHILD WITH ACUTE LYMPHOBLASTIC LEUKEMIA: A CASE REPORT - Akhlaque, Uzma; Ayaz, Saeed Bin (Journal of Postgraduate Medical Institute, 2020)
Development of acute motor axonal neuropathy (AMAN) in children with acute lymphoblastic leukemia (ALL) is a rare phenomenon and needs to be differentiated from neuropathy induced by chemotherapeutic agents as both require different treatment protocols. The later may warrant adjustments in the chemotherapy regimen. Electrodiagnostic (EDX) studies play the key role in this differentiation. We report here an 11-year-old girl with ALL who presented with signs and symptoms of a rapidly progressive neuropathy diagnosed as AMAN through EDX studies, and achieved a better recovery following timely immunomodulatory therapy, electrical muscle stimulation of the key muscle groups, and therapeutic exercises. The differentiation between AMAN and chemotherapeutics' induced neuropathy through EDX studies is important in children with ALL to initiate timely immunomodulatory therapy for AMAN and avoid unnecessary withdrawal of chemotherapeutic agents.